Information and Communication Technologies and the Right to Informational Privacy in Health Care: A Comprehensive Analysis - Nandu Sam Jose (Brawijaya Law Journal, 2023)
The rapid integration of information and communication technologies (ICTs) into the healthcare field has led to significant advancements, including the development of electronic health records, telemedicine, big data analytics, and artificial intelligence. These technologies have revolutionized medical care by improving accessibility, enhancing quality, and facilitating personalized treatments. However, with these advancements, the issue of health information privacy has become increasingly prominent. This article examines the interplay between ICTs and the right to informational privacy in the healthcare field. More specifically, it explores the core principles of informational privacy by outlining its legal and ethical facets while also underscoring the importance of maintaining the confidentiality and security of personal health information (PHI). The essay also examines the challenges threatening informational privacy—including data breaches, inadequate regulatory frameworks, and ethical dilemmas surrounding big data and AI. Simultaneously, the article identifies opportunities for enhancing privacy protections, including introducing technological innovations, and strengthening legal and regulatory frameworks. The piece also offers practical recommendations for various stakeholders—such as policymakers, healthcare providers, and individuals—for ensuring the protection of PHI. In conclusion, this article emphasizes the importance of striking a delicate balance between leveraging the benefits of ICTs and protecting informational privacy, which is a prerequisite for fostering a resilient, equitable, and patient-centered healthcare system.